The Influence of Flannel Board Media on the Ability to Recognize Letters in Syllables in Children Aged 4–5 Years - Yasmine, Safitri Tiara; Fitri, Ruqoyyah; Fairuzillah, Muhammad Naufal; Widayati, Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the effect of flannel board media on the ability to recognize letters in syllables in children aged 4–5 years. This research employed a quantitative approach with a quasi-experimental method and a one-group pretest–posttest design. The research subjects were 8 children in Group A at TK At-Taqwa Bojonegoro. Data collection techniques used observation sheets, and data analysis was carried out using the Mann-Whitney U test. The results showed that there was a significant effect of using flannel board media on the ability to recognize letters in syllables, as indicated by the significance value (Asymp. Sig. 2-tailed) of 0.001 < 0.05 based on the Mann-Whitney U test. Thus, it can be concluded that flannel board media is effective for use in language learning for early childhood.